The Process of Composition/Joy M .Reid - Reid, Joy M (2000)
This series takes students from beginning-level instruction on basic sentence structure through the development and production of advanced academic papers.
1.The Fundamentals of writing 2.Making Decisions in the writing process 3.Planning the Essay
incluye índice
Col. Educ
Keywords: 1.WRITTEN RESPONSES 2.PERSUADING AN AUDIENCE 3.GRAMMATICAL